2013
DOI: 10.1039/c3nr00444a
|View full text |Cite
|
Sign up to set email alerts
|

Well-dispersed Co3O4/Co2MnO4 nanocomposites as a synergistic bifunctional catalyst for oxygen reduction and oxygen evolution reactions

Abstract: Co3O4/Co2MnO4 nanocomposites, derived from a single-source CoMn-layered double hydroxide precursor, exhibit excellent bifunctional oxygen electrode activities for both oxygen reduction and evolution reactions, which can be attributed to the large specific surface area and well-dispersed heterogeneous structure of the nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
147
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(156 citation statements)
references
References 24 publications
8
147
0
1
Order By: Relevance
“…It was found that the average film thickness of Co 3 O 4 electrodeposited on FTO substrate is approximately 200 nm. Figure 6b shows the profilometry analysis of the surface of film FS 10 and it is possible to observe that a height value of approximately 230 nm was registered, which is similar with the obtained in analysis by GDS. The insert in Figure 7 shows the simplified Randles circuit model, that combines the high frequency resistance of the electrolyte, ionic charge transfer resistance and double layer capacitance at the front contact, and restricted diffusion of the inserted species.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…It was found that the average film thickness of Co 3 O 4 electrodeposited on FTO substrate is approximately 200 nm. Figure 6b shows the profilometry analysis of the surface of film FS 10 and it is possible to observe that a height value of approximately 230 nm was registered, which is similar with the obtained in analysis by GDS. The insert in Figure 7 shows the simplified Randles circuit model, that combines the high frequency resistance of the electrolyte, ionic charge transfer resistance and double layer capacitance at the front contact, and restricted diffusion of the inserted species.…”
Section: Resultssupporting
confidence: 68%
“…In this way, it is important to notice that the use of Co-glycine complexes allows the obtaining of semi-spherical morphologies of Co 3 O 4 electrodes. Figure 6a shows a typical GDS elemental composition profile of the film FS 10 . It was found that the average film thickness of Co 3 O 4 electrodeposited on FTO substrate is approximately 200 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(7)(8)(9)(10)(11)(12)(13)(14) Among transition metal oxides, Mn-based oxides and particularly spinels have shown outstanding performance for ORR and, to a minor extent, for OER. (7,(15)(16)(17)(18)(19)(20)(21) Besides, Co-based oxides are excellent electrocatalysts for OER, (22)(23)(24)(25) However, the multiple valence and related structural variability of transition metal oxides, which is at the origin of their exceptional electrocatalytic performance, is also behind the difficulty to produce these compounds in a reproducible and controlled manner. This is a particularly important limitation when taking into account the strong dependence of the physicochemical properties of transition metal oxides on composition, structural parameters, and distribution and oxidation state of cations.…”
Section: Introductionmentioning
confidence: 99%